Do maximally entangled states always have an advantage over non-maximally entangled states in Schwarzschild black hole? - Shu-Min Wu; Si-Han Li (European Physical Journal C: Particles and Fields)
Abstract It is generally believed that quantum entanglement in the maximally entangled states is greater than quantum entanglement in the non-maximally entangled states under a relativistic setting. In this paper, we study quantum entanglement for four different types of Bell-like states of the fermionic modes near the event horizon of a Schwarzschild black hole. It is interesting to find that quantum entanglement in the maximally entangled states is less than quantum entanglement in the non-maximally entangled states in Schwarzschild spacetime. From the perspective of quantum resources, the non-maximally entangled states may have more advantages in curved spacetime compared to the maximally entangled states. This is obviously different from the conclusions in previous paper. For two types of Bell-like states, quantum entanglement suffers sudden death under the Hawking effect of the black hole, and for the other two types of Bell-like states, quantum entanglement can exist forever regardless of the Hawking temperature. Therefore, we should choose appropriate types of Bell-like states to handle relativistic quantum information tasks.